2015
DOI: 10.1016/j.jds.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cryogun cryotherapy is the first-line treatment of choice for oral leukoplakia

Abstract: Oral leukoplakia (OL) is the most common oral precancerous lesion. Histologically, approximately 90% of OL lesions show hyperkeratosis and/or epithelial hyperplasia, 5% show epithelial dysplasia or carcinoma in situ, and another 5% show invasive carcinoma. The malignant transformation rates of OL lesions have been reported to be 1e7% for homogenous thick leukoplakia, and 4e15% for granular or verruciform leukoplakia. 1e3 The relatively high malignant transformation rates of OL lesions highlight the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Cheng SJ, Chen HM, Chiang CP. [8] were found that topical 5-aminolevulinic acid-mediated photodynamic therapy (topical ALA-PDT) is very effective for oral erythroleukoplakia and oral verrucous hyperplasia lesions, but is less effective for OL lesions. However, when topical ALA-PDT is combined with cryotherapy, the combination therapy may be an effective treatment modality for OL lesions.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Cheng SJ, Chen HM, Chiang CP. [8] were found that topical 5-aminolevulinic acid-mediated photodynamic therapy (topical ALA-PDT) is very effective for oral erythroleukoplakia and oral verrucous hyperplasia lesions, but is less effective for OL lesions. However, when topical ALA-PDT is combined with cryotherapy, the combination therapy may be an effective treatment modality for OL lesions.…”
Section: Treatment Methodsmentioning
confidence: 99%